Pull-out analysis of laser modified polyamide tire cords through rubber matrix. (October 2017) - Niroomand, Mahyar; Hejazi, Sayyed Mahdi; Sheikhzadeh, Mohammad; Alirezazadeh, Azam
Abstract: Today with regard to the increased tire failure accidents, strengthening the tire cord adhesion to rubber compounds to reduce the tire blow-out risks is being of great importance. The main aim of this research is strengthening the adhesion of tire cord to the plastic/rubber matrix by the use of laser treatment method to achieve a high performance material. In this study, the polyamide (known as nylon 66) tire cord was prepared and the surface treatment was performed by CO2 laser, prior to Resorcinol formaldehyde latex (RFL) dipping. To obtain the ideal irradiation condition, surface roughness was evaluated by image analysis using both Fractalyse2.4 and Mountainsmap7 Software. The cord parameters such as count, twist, strength and toughness and also H-Test, FTIR and XRD analysis were tested before and after laser treatment. The results showed that cord count, twist and strength did not have any significant changes. However, the other parameters such as cord elongation, shrinkage and toughness were changed so that enhanced adhesion properties. FTIR and XRD analysis revealed that the crystalline structure of irradiated cords has been decreased. The results showed that laser treatment increases the interfacial shear strength of rubber/fiber without reducing strength of cords. Finally, a mechanical model of failure based on pull-out method was used to investigate the effect of laser treatment on the adhesion strength of cord/rubber. Thus, an index of laser intensity was introduced which would be capable of predicting the influence of any laser treatments on interfacial shear strength between cords and rubber. Highlights: The adhesion strength of nylon 66 cord/rubber was increased by using CO2 laser. Laser affected surface roughness, chemical bonds and crystalline structure of nylon. Laser did not affect cord count, strength and twist. Shrinkage, elongation and toughness of cords have significantly changed. A mechanical model was introduced based on modifying Gent energy equations.